Desafios na institucionalização de “sistema de custeio” em uma instituição federal de ensino superior: o caso da Universidade Federal do Espírito Santo - Souza, Valber Lugao de (2019)
Predominantly used in market organizations, cost accounting has established itself in public administration as an essential tool for control in any organization by producing information for managers to support better decision making. This research is guided by the following question: What are the most relevant challenges and difficulties in the process of institutionalizing a cost system in a Federal Higher Education Institution? The objective is to understand the difficulties, from the institutional point of view, in the formal implementation and also in the institutionalization - cultural reception by the involved publics - of a cost system at the Federal University of Espírito Santo (UFES), from 2011 to 2019. This research is based on a literature review on the subject and is based on the Institutional Theory. This is a qualitative research using the technique of Content Analysis. Data and information are obtained through interviews with technicians and managers who work in the area of cost accounting, seeking to obtain answers to the research problem and the achievement of its objective. Subsidiarily, the documentary analysis is used within the researched space. The dissertation's product is covered by its specific objectives of understanding the institutionalization phases of the cost system implementation processes at UFES and offering support for the elaboration of a proposal to solve the problems that involve these processes and in the elaboration of the institutionalization resolution proposal. of a cost system in an IFES. The results indicate that the main challenges are of order, that UFES has a long way to go in the effective implementation of a cost system for the University. Noteworthy is the search for a cost system for the University as well as the training and mobilization of the servers that will work as the University cost system. The plus point is your staff. From the perspective of institutional theory, it can be concluded that of the researched factors, cost accounting was not institutionalized. And that this management tool so important for management control, is still only used sparingly and not completely.